Postmodern music / Postmodern thought - Lochhead, Judy; Auner, Joseph (New York Routledge, 2002)
What is postmodern music and how does it differ from earlier styles, including modernist music? What roles have electronic technologies and sound production played in defining postmodern music? Has postmodern music blurred the lines between high and popular music? Addressing these and other questions, this ground-breaking collection gathers together for the first time essays on postmodernism and music written primarily by musicologists, covering a wide range of musical styles including concert music, jazz, film music, and popular music. Topics include: the importance of technology and marketing in postmodern music; the appropriation and reworking of Western music by non-Western bands; postmodern characteristics in the music of Gorecki, Rochberg, Zorn, and Bolcom, as well as Bjork and Wu Tang Clan; issues of music and race in such films as "The Bridges of Madison County, Batman, Bullworth, " and "He Got Game;" and comparisons of postmodern architecture to postmodern music. Also includes nine musical examples.